2015
DOI: 10.3748/wjg.v21.i7.2030
|View full text |Cite
|
Sign up to set email alerts
|

Negative impact of bone-marrow-derived mesenchymal stem cells on dextran sulfate sodium-induced colitis

Abstract: AIM:To investigate the effects of mesenchymal stem cells (MSCs) on dextran sulfate sodium-induced inflammatory bowel disease (IBD).METHODS: C57BL/6 mice were fed 3.5% (g/L) dextran sulfate sodium. On day seven, the mice received intraperitoneal injections of 1 × 10 6 MSCs. The survival rate, disease activity index values, and body weight, were monitored daily. On day ten, colon lengths and histopathologic changes were assessed. In addition, immunoregulatory changes following MSC administration were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In pre-clinical studies, MSCs were hypothesized to exert immunomodulatory effects that would improve the pathogenesis of IBD. Previously, we reported for the first time that MSCs are not clinically beneficial in IBD treatment ( 72 ). Other pre-clinical studies have suggested the positive outcomes of MSCs for the treatment of IBD; however, in these studies, MSCs were not used alone, but rather genetically modified to IL-12p40 ( 73 ), coated with antibodies ( 74 ), or genetically depleted with autoimmune regulators ( 75 ).…”
Section: Discrepancy Between Expected and Actual Results Of Msc Efficmentioning
confidence: 99%
“…In pre-clinical studies, MSCs were hypothesized to exert immunomodulatory effects that would improve the pathogenesis of IBD. Previously, we reported for the first time that MSCs are not clinically beneficial in IBD treatment ( 72 ). Other pre-clinical studies have suggested the positive outcomes of MSCs for the treatment of IBD; however, in these studies, MSCs were not used alone, but rather genetically modified to IL-12p40 ( 73 ), coated with antibodies ( 74 ), or genetically depleted with autoimmune regulators ( 75 ).…”
Section: Discrepancy Between Expected and Actual Results Of Msc Efficmentioning
confidence: 99%
“…A key factor often ignored by researchers is that the physiological oxygen concentration in the bone marrow varies from 1% to 7%. Although low-oxygen culture conditions have been recognized to exert an important impact on BM-MSCs, mouse BM-MSCs are cultured in 21% oxygen condition in many studies [ 2 , 7 , 8 , 17 , 30 32 ]. Here, we compared cell proliferation, clonogenicity, and surface markers between 21%, 10%, and 5% oxygen conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Forte et al (40), human umbilical cord MSCs were used to treat acute trinitrobenzene sulfonic acid-induced UC. In another study, the inflammatory markers such as IL-17, IL-23, IFN-γ and IL-6 were measured to assess the therapeutic efficacy of human umbilical cord MSCs and were shown to be significantly decreased in the treated mice (41). In the present study, during the follow-up, the levels of cytokines in group I, including TNF-α, IL-6 and IFN-γ, were not significantly changed compared with group II.…”
Section: Discussionmentioning
confidence: 99%